Public Service Interactions and Patient Satisfaction: The Influence of Healthcare Worker Performance at Masohi Regional General Hospital, Central Maluku Regency - Melisa Karim Mahu; Petronela Sahetapy; Jeanly Waisapy (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the Study: This study examines the influence of healthcare worker performance on patient satisfaction at Masohi Regional General Hospital, Central Maluku Regency, by positioning hospital care as a public service interaction shaped by social relations, patient perceptions, communication, and trust. Methodology: This study used a quantitative explanatory design. Data were collected from 50 patients through accidental sampling using a structured questionnaire measured with a five-point Likert scale. Validity and reliability testing, simple linear regression, t-test, and coefficient of determination analysis were conducted using statistical software. Main Findings: The findings show that healthcare worker performance has a positive and statistically significant influence on patient satisfaction. This result indicates that patient satisfaction is not only a managerial indicator, but also a social expression of trust, perceived fairness, respect, responsiveness, and the quality of interaction between citizens and public service providers. In a regional public hospital, timely service, empathy, clear communication, and professional behavior shape patients' experiences of access, dignity, and confidence in public institutions. Novelty/Originality of This Study: This study contributes to social science and public administration literature by interpreting patient satisfaction as a social outcome of public service relations rather than merely a medical service indicator. It provides contextual evidence from a regional public hospital in eastern Indonesia, where resource limitations, post-pandemic pressures, and unequal access shape patient experiences and expectations.